Porphyry's On the cave of the nymphs in its intellectual context - Akçay, K. Nilüfer (Brill, 2019)
Introduction – Allegory as a way of thinking in On the cave of the nymphs – The cave as symbol and image of the cosmos – Embodiment – The path towards the immortality of the soul – Conclusion
10.1163/9789004408272
Keywords: Porphyry; Peri tou en Odysseia tōn nymphōn antrou; Neoplatonism; Allegory